2016
DOI: 10.1007/s40094-016-0213-0
|View full text |Cite
|
Sign up to set email alerts
|

On the corrosion resistance of AISI 316L-type stainless steel coated with manganese and annealed with flow of oxygen

Abstract: AISI 316L-type stainless steel was coated with 300-nm-thick Mn thin films and post-annealed at 673 K with a constant flow of oxygen (250 cm 3 /min). The films crystallographic and morphological structures were analyzed using X-ray diffraction (XRD) and atomic force microscopy (AFM) before corrosion test and scanning electron microscopy (SEM) after corrosion test. Corrosion behavior of the samples in 0.3, 0.5 and 0.6 M NaCl solutions was investigated by means of potentiodynamic and electrochemical impedance spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The surface morphology of the samples was measured using atomic force microscopy (AFM), while X-ray diffraction (XRD) study of the samples provided the crystal structure. Kramers-Kronig transformation analysis of the results confirmed the EIS data [24,25].…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…The surface morphology of the samples was measured using atomic force microscopy (AFM), while X-ray diffraction (XRD) study of the samples provided the crystal structure. Kramers-Kronig transformation analysis of the results confirmed the EIS data [24,25].…”
Section: Introductionsupporting
confidence: 65%
“…Their results showed that the Mn-nitride coating improved the corrosion resistance of the stainless steel substrate in the saline solution by forming an effective barrier between the substrate and the corroding medium. In another research, Savaloni et al [25] investigated the corrosion resistance of AISI 316L-type stainless steel coated with a Mn-oxide coating with 300 nm thickness in 0.3, 0.5, and 0.6 M NaCl solutions. Their results showed that the corrosion resistance of coated samples in different saline solutions is improved relative to the bare samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molybdenum is added to improve its corrosion resistance against chlorides. Stainless steel 316 is one of the most used materials in industries such as gas, offshore platforms, and many others due to its low price and active passive behavior [11][12][13]. It was constructed in a rectangular shape to support the electronic and motor components.…”
Section: Structural Materialsmentioning
confidence: 99%
“…Their results show that the hybrid coating increases the corrosion resistance of 316L stainless steel in chloride environments. Also, Savaloni et al investigated the effect of Mn coating on corrosion resistance of 316L stainless steel in the solutions containing 0.3, 0.5, and 0.6 mol/L of NaCl by potentiodynamic polarization and EIS techniques. Their results showed that in all these solutions, the corrosion resistance of 316L stainless steel coated with Mn is higher than that of the steel without coating.…”
Section: Introductionmentioning
confidence: 99%